Teaching Speaking Report Text Using Speaking Prompt - Sunarti Sunarti (Journal of ELT, Linguistics, and Literature, 2015)
Learning a language means learning how to communicate either in oral or written way, that is how to listen, speak, read and write fluently, accurately and acceptaby. However students find difficulties in learning them. In speaking session, the students can not express their idea well because they have problems in vocabulay, putting the words together in the correct structure, and pronouncing them besides they are lack of information or they don’t have enough background knowledge about the topic. Those problems makes the students don’t want to speak, or they need long time to prepare their speaking. Another problem is that they are accustmed to write before speaking and memorize it to perform their speaking task. Based on these problems it is necesary to use the teaching strategies, one of them is using speaking promt. As pre activity, the teacher reviews the generic structure, the simple present tense, shows pictures related to the topic, introduces the facts which are classified based on the generic structure, and pronunciation practise. In the main activy, students describe the picture based on the facts that have been given.The sentence pattern of simple present tense is also shown. As the post activity, the students give comment on their performance each other.These activities in fact can solve their problems. Speaking prompt helps them in speaking. They don’t need to think about the background knowledge, the generic structure and the sentence pattern.